Evaluation of ALON for Proton Shielding of Low Earth Orbit (LEO) Satellite Solar Arrays - Firat, C. (Atom Indonesia, 2026)
This study evaluates the proton radiation shielding efficacy of various materials, with a focus on ALON, for satellite solar arrays in LEO across the 0.1-200 MeV energy range using SRIM/TRIM simulations. Key metrics, ion penetration, vacancies per ion, range, displacements per atom, non-ionizing energy loss, Bragg curves, and transmission, were analyzed for aluminum, SiO2, polyimide, ALON, and Ta2O5/Al2O3 at thicknesses from 0.01 mm to 4 mm. ALON demonstrates moderate stopping power and damage resistance, with penetration exceeding 20 µm and 100 µm at 0.5 MeV and 5 MeV, respectively, and 2000 µm and 4000 µm providing protection up to 50 MeV and 100 MeV, while maintaining high optical clarity (>80%) for photovoltaic (PV) applications. Thinner layers mitigate high-energy proton damage but are vulnerable to low-energy (